Nutritional characteristics and physiological studies on the growth and development of Phlebiopsis gigantea - negi, sushma; Prasher, Indu Bhushan; Kumar, Rajeev (Current Botany, 2017)
Physiological studies pertaining to the effect of physical factors, carbon and nitrogen requirement of Phlebiopsis gigantea were conducted to know its behaviour in vitro. These studies have revealed interesting results regarding its growth and reproduction behaviour. The best medium for the optimum growth is Glucose-peptone medium. The optimum temperature (28Â°C) and pH (5.0) is required for the optimum mycelial production of Phlebiopsis gigantea after 12 days of incubation. The best carbon source for the growth of the fungus is D(+)Glucose least seen in Sucrose medium. The best inorganic nitrogen sources for the growth of the fungus is Sodium nitrate. The least mycelial growth of fungus is observed in ammonium acetate and ammonium nitrate. The best organic nitrogen compound for the mycelial growth of fungus is DL-threonine.